The Role of Project-Based Learning in Motivation, Collaboration, and Achievement in Second Language Acquisition - Muho, Anita; Leka , Klodiana; Sivakumar, Ramaraj; La Ragione, Colomba; Weiss, Ervín (Journal of Education Culture and Society, 2025)
Aim. This study aims to explore how project-based learning (PBL) influences student motivation, collaboration, and academic achievement in second-language education. In particular, the study aims to examine whether PBL enhances students’ language abilities by promoting a more engaging learning environment and fostering improved classroom management. Methods. The quantitative part of the study involved a sample of 250 students from six high schools in Albania, specifically located in Tirane, Elbasan, and Shkoder. The qualitative aspect involved conducting interviews with 16 teachers who were from the same schools. A combination of student surveys for quantitative data and teacher interviews for qualitative insights was employed using a mixed-method approach. The analysis focused on the effects of PBL on student motivation, collaboration, and academic performance, particularly among students in the lower percentile group. Results. The findings revealed that while the overall academic achievement in second language acquisition was not significantly improved, students in the lower percentile group showed a notable increase in motivation and achievement, particularly in collaborative tasks. The study also found that PBL encouraged a more dynamic classroom environment and enhanced student engagement, even in cases where academic performance remained unchanged. Conclusion. Despite the lack of a significant impact on overall academic achievement, project-based learning has the potential to improve student motivation and collaborative skills in second language acquisition. The research proposes practical suggestions for teachers to include more collaborative activities in their instruction and encourages more investigation into how various forms of PBL impact language learning results.